Visualizing the Impact of COVID-19 in the Mobility Dynamics - Alpalhão, Nuno (2021)
Alpalhão, N., Neto, M. D. C., & Motta, M. (2022). Visualizing the Impact of COVID-19 in the Mobility Dynamics: A Dashboard Framework for Decision Support in Smart Cities. In S. Shirowzhan (Ed.), Data Science, Data Visualization, and Digital Twins (pp. 1-12). IntechOpen. https://doi.org/10.5772/intechopen.96295